Is Lying Bound to Commitment? Empirically Investigating Deceptive Presuppositions, Implicatures, and Actions. Issue 2 (22nd February 2021) - Reins, Louisa M.; Wiegmann, Alex
Abstract: Lying is an important moral phenomenon that most people are affected by on a daily basis—be it in personal relationships, in political debates, or in the form of fake news. Nevertheless, surprisingly little is known about what actually constitutes a lie. According to the traditional definition of lying, a person lies if they explicitly express something they believe to be false. Consequently, it is often assumed that people cannot lie by more indirectly communicating believed‐false claims, for instance by merely conversationally implicating them. In this paper, we subject this claim to an empirical test. In a preregistered study of 300 participants, we investigate how people judge cases of implicit deceptions that would usually be excluded by the traditional definition of lying (i.e., conversational implicatures, presuppositions, and nonverbal actions). Our results show that people do in fact consider it possible to lie by indirect means, suggesting that people have a broader concept of lying than is usually assumed. Moreover, our findings indicate that lie judgments are closely tied to the extent to which agents are perceived as having committed themselves to the believed‐false claims they have communicated. We discuss the implications of our results for the traditional definition of lying and propose a new commitment‐based definition of lying that can account for the findings of our experiment.